Descripción y optimización de un esquema dirty paper coding - Diego Mauricio Camargo Casas (Tecnura, 2013)
This paper presents a precoding technique, known as "Dirty Paper Coding", which allows transmission with limited levels of power over channels where the interference level is known by the transmitter. The interference levels considered have finite variance - just like in MIMO (multiple-input and multiple-output) communications, where there is ISI (inter-symbol inter¬ference), Intra-Cell and Inter-Cell interference among other types of interference. The role of proper scaling parameters at the transmitter and receiver is described. Such parameters make use of a linear estimator that minimizes the mean square error of the signals involved. Moreover, a quantization scheme equivalent to a module operation is explained in detail. The purpose of this scheme is to pre-cancel the interference at the transmitter, showing that interference knowledge is used by the encoder as much as possible, namely the encoder attempts to adapt itself to the interference value. Thus, it is possible to decode the signal to make it look almost like the original signal since the new signal is now totally independent of interference.